Analisis Kebutuhan Ruang Parkir di Kawasan Palembang Square Mall - Yules Pramona Zulkarnain (UNIVERSITAS TRIDINANTI PALEMBANG, 2013)
Palembang Square Mall is located in Angkatan 45 Palembang. It is one of thebiggest Mall in Palembang. Angkatan 45 street is an primary way in Palembang. Strategiclocation makes Palembang Square Mall has a lot of customers from the origin people orthe people from out of town. Palembang Square Mall which is located in the centre ofbusiness area in Palembang has 5,4ha it is devided into 50.000m2 as a building.The parkinglot is located around the both building that. The land road which is used as the parking lotinvolves : Kampus POM IX street, Sumpah Pemuda street and Kapten A. Rivai street. Thatphenomena is caused by enough parking facility for vehicles that visit Palembang SquareMall and the lowly realization of the Mall visitors or the users. So it causes traffic disturbencein Angkatan 45 street and the street around the Mall. This matter can be seen fromdisorganized traffic in Palembang Square Mall either for those who are going to enter, lookfor the parking lot or for those who are going to leave from that area so, one of theproblems caused is the traffic jam and uncomfortable feeling. From that analysis, it canmake a hypotesis as follow : 1. The vehicle owners who visit there tend to choose the easyand the fast parking lot as on follow street. 2. The undiciplined road users and the mixedof public transportations which are entered in the system (in the lane around the Mall),and the limited of parking lot comparing with the height of parking volume, and a badparking management become the caused of disorganization and the traffic jam around theMall.The survey method in this research is using a primary data collection toward the parkingdemand ( come, wait and leave from the system ) by Mall visitors to analyse the arrival rate( ë ) and parking rate ( μ ). A secondary data is used to predict the demand of parkinginvolves : the population, PDRB, vehicle ownership and the amount of parking it self .In 2013, the amount of car peraday where parked in Palembang Square Mall is 3600 forcar and 2550 for motorcycle. From this analysis, it can be concluded that the optimalparking capacity is 750 for cars and 890 for motorcycles. While the parking lot that isprovided is only 645 for cars and 786 for motorcycles, so existing parking lot is not enough.From the prediction, the amount of vehicles that sure parked in Palembang Square Mallper day in 2020 is 7.270 for cars and 4.750 for motorcycles, with the necessity of parkinglot as 1.520 for cars and 1.660 for motorcycles. From the calculation of Total Cost Programsit can get that the optimal parking rate is Rp. 5000,00 for car and Rp. 2.000,00 formotorcycle.Keyword : Parking demand, Arrival Rate ( ë ) and Parking Rate (μ ), Total Cost ( C ) andthe Optimal Parking Rate.